(untitled) (Journal of Applied and Natural Science, 2018)
To improve the feed quality removal of lignin from plant biomass is essential. To improve the activity of laccase of white rot fungi, aromatic inducers are used. In this study three inducers [Resorcinol (5mM and 10mM), Xylidine and Anisaldehyde] to induce the production of laccase enzyme in the culture of fungus: Cyathus stercoreus. Resorcinol (10mM) was found to be the best inducer among the rest. The enzyme activity was observed highest on the 8th day of induction (226.7U/ml). Protein content was also increased with the age of the culture. 80% ammonium sulphate was suitable for precipitating the laccase enzyme for culture filtrate. The laccase production can be enhanced with inducers and can be further used for the removal of lignin from the plant biomass.